2002
DOI: 10.1034/j.1600-9657.2002.00092.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of post‐traumatic PDL cells viability by a novel collagenase assay

Abstract: Both length of extra-alveolar time and type of storage media are significant factors that can affect the long-term prognosis for replanted teeth. Numerous studies have examined various media in an attempt to determine the ideal material for storage of the avulsed tooth. The purpose of this study was to compare the number of viable periodontium ligament (PDL) cells in different storage media using a collagenase assay. Thirty-three freshly extracted human teeth were divided into four experimental and two control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
75
0
6

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(82 citation statements)
references
References 16 publications
1
75
0
6
Order By: Relevance
“…This procedure allowed rapid cell retrieval and maintained maximum cellular integrity, as was demonstrated by the positive control samples (3,10,41).…”
Section: Sukob Interesamentioning
confidence: 99%
See 1 more Smart Citation
“…This procedure allowed rapid cell retrieval and maintained maximum cellular integrity, as was demonstrated by the positive control samples (3,10,41).…”
Section: Sukob Interesamentioning
confidence: 99%
“…They have been successful in preserving the viability of the PDL fibers for extended periods (24). Whereas storage media was a topic of research interest (25)(26)(27)(28)(29)(30)(31), the critical extraoral dry time of PDL had been investigated in several studies (3,10,30,(32)(33)(34)(35)(36) where time frames of 30 min or 45 min are appreciable. Forty-five minute time period was chosen as it allows for comparison with previous investigations.…”
Section: Sukob Interesamentioning
confidence: 99%
“…For the critical outcome of viability, we identified very-lowquality evidence (downgraded for risk of bias, indirectness, and imprecision) from 1 observational study, 177 but the MD for cell viability was not estimable (mean percentage of 45.17±12.03 SD for intervention group compared with the mean percentage of 90.59±3.77 SD for control group).…”
Section: Tap Water (I) Compared With Milk (C)mentioning
confidence: 99%
“…We identified very-low-quality evidence (downgraded for indirectness and imprecision) from 1 observational study 180 with 24 teeth in which benefit for cell viability was not shown after 2 hours of immersion (MD, −161 000; 95% CI, −362 186.91 to 40 186.91). We identified very-low-quality evidence (downgraded for indirectness and imprecision) from 2 other observational studies 174,177 in which the MD for cell viability was not estimable (median difference 376 000; mean percentage of 77.8±2.92 SD for intervention group versus mean percentage of 90.59±3.77 SD for control group).For the critical outcome of viability (periodontal healing), we identified very-low-quality evidence (downgraded for risk of bias and imprecision) from 1 observational study 181 with 25 avulsed teeth showing no benefit (RR, 0.99; 95% CI, 0.48-2.04).For the critical outcome of success of reimplantation (replacement resorption and extraction due to replacement resorption), we identified very-low-quality evidence (downgraded for risk of bias and imprecision) from 1 observational study 181 with 25 avulsed teeth showing no benefit (RR, 1.07; 95% CI, 0.33-3.46; and RR, 0.89; 95% CI, 0.09-8.50, respectively). …”
mentioning
confidence: 99%
“…7,10,[12][13][14][15][16]18,20,21 • Suero fisiológico: Tiene una osmolalidad de 280 -285 mOsm/ Kg, un pH de 7,0 13,18 y es estéril, por lo que es un medio de conservación aceptable a corto plazo, manteniendo la vitalidad celular unas tres horas. 3,7,11,14,18,19,24,26 • Solución balanceada de HanK's (HBSS): Es un medio de cultivo estándar usado en la investigación biomédica para la conservación celular. Tiene un pH de 7,2 y su osmolalidad es de 270 -320 mOsm/Kg 8,19 , evita la reabsorción radicular en un 91 %.…”
Section: -28unclassified